Optimal Power Allocation Algorithm for Radar Network Systems Based on Low Probability of Intercept Optimization(in English) - Shi Chen-guang; Wang Fei; Zhou Jian-jiang; Chen Jun (Leida xuebao, 2014)
A novel optimal power allocation algorithm for radar network systems is proposed for Low Probability of Intercept (LPI) technology in modern electronic warfare. The algorithm is based on the LPI optimization. First, the Schleher intercept factor for a radar network is derived, and then the Schleher intercept factor is minimized by optimizing the transmission power allocation among netted radars in the network to guarantee target-tracking performance. Furthermore, the Nonlinear Programming Genetic Algorithm (NPGA) is used to solve the resulting nonconvex, nonlinear, and constrained optimization problem. Numerical simulation results show the effectiveness of the proposed algorithm.